The Impact of Maternal Parenting Stress on Maternal Resilience. A Study With Greek and Cypriot Mothers - Dimitriou, Loucia; Keramioti, Lydia; Panaoura, Rita (Calitatea Vieții, 2024)
When people become parents, they experience significant life changes. These include feelings of joy and satisfaction, but simultaneously, the parental role comes with obstacles and obligations added to many people’s already challenging daily routines. The present study was focused on mothers, and examined the impact of maternal parenting stress on psychological resilience, by considering demographic characteristics such as age, education, employment status, and grandparental support system. We conducted a quantitative, web-designed survey with a sample of 151 mothers of children in various age groups (from 1‒12 years old), from Greece and Cyprus, who were 18+ years old. Participants completed the CD-RISK online (Connor and Davidson 2003), the Parental Stress Scale (Berry and Jones 1995), and a personal information form (PIF) with demographic information. Results indicated that mothers experienced parenting stress at moderate to high levels, even if their resilience was positively or negatively influenced by other factors, such as the participation of others (grandparents) in the care of their children. Findings also showed that mothers experienced parental stress as an independent factor in resilience. It seems like providing practical social support structures for mothers aged 26‒45 and single mothers could contribute positively to alleviating their stress symptoms.